A broad stroke or different strokes for different folks? Examining the subtleties in crisis management approaches in state-owned enterprises and privately owned enterprises in China. Issue 1 (2nd January 2018) - Pang, Augustine; Hu, Yang; Woon, Eugene
Abstract : Several previous studies have been conducted to examine China's management of internal crises, but few have investigated the approaches to crisis management used by domestic Chinese organizations. It is critical to study these organizations because their approaches exemplify the intricacies of crisis management at the local level. In China, there are two main types of organizations: state-owned enterprises (SOE) and privately owned enterprises (POE). This study aimed to determine how their business orientations led to different styles of crisis management in terms of media relations, government relations, and crisis responses. The findings showed that SOEs sought shelter from the government, whereas the POEs sought goodwill from the government. The SOEs sought to control the media, whereas the POEs sought to circumvent media exposure. The SOEs predominantly employed the barnacle strategy in their crisis responses and occasionally used third-party endorsements and set up new topics, whereas the POEs employed third-party endorsements and set up new topics.